Black Rice Cultivation in India – Prospects and Opportunities - Saha, Sanjoy; Vijayakumar, S.; Saha, Sanjana; Mahapatra, Ashirbachan; Kumar, R. Mahender; Sundaram, R. M. (Chronicle of Bioresource Management, 2023)
Black rice is known for its high nutritional value and is a source of iron, vitamin E, antioxidants, calcium, magnesium, zinc and contains more protein than brown rice. In India, it is grown in a large area in Manipur for a long time and is popularly known as Chak-hao, and desserts made from black rice are served as major feasts. As such, it offers several health benefits, including boosting eye and heart health, protection against certain forms of cancer, and aiding weight loss. Black rice is a healthier alternative to white rice that can be used in all of the same ways. There are great prospects to promote black rice cultivation in major rice-growing states of India and doing so will help our country to achieve nutritional security.